THE POWER WITHIN: A BRIEF ON MICHEL FOUCAULT’S IDEAS OF EDUCATION AND SOCIAL THEORY - Fery Fahrudin Yunus (P3M STAIN Kudus, 2016)
Social theories generally defined as analytical frameworks or paradigms that applicable to examine social phenomena. The term belonging to ideas about how societies change and develop, methods of explaining social behaviour, power and social structure. In contemporary social theory, certain themes such as the nature of social life, the relationship between self and society, the structure of social institutions, social transformation, as well as such as gender, race, class, and others themes consider as most priority to others. This paper will demonstrates Foucault’s ideas in structures and discourses—how discourses produced particular truths which studying institutions (schools) and offering a critique of what was considered to be normal, to consider Foucault’s ideas such as panopticism to examine disciplinary and self-policy of schools. The main purpose ofthis paper is to find practical value in Foucault’s ideas.